Analytical and Numerical Analysis of the Squeezed Unsteady MHD Nanofluid Flow in the Presence of Thermal Radiation. (31st March 2022) - Ullah, Hakeem; Khan, Muhammad Arif; Fiza, Mehreen; Ullah, Kashif; Ayaz, Muhammad; Al-Mekhlafi, Seham M.
Abstract : In this study, the unsteady squeezing nanofluid flow between two plates with thermal radiation has been investigated. The governing equations of the flow model have been transformed to a set of nonlinear ordinary differential equations (ODEs) from a set of partial differential equations (PDEs) using a suitable similarity variable. The optimal auxiliary function method (OAFM) and Runge–Kutta method of order 4 (RK method of order 4) are used for the solution of the modeled problem. The variation of the squeezing number, Prandtl number, Eckert number, and thermal radiation has been presented. The magnetic field resists the flow velocity, and the Prandtl number resists the temperature distribution. The increase in volume fraction decreases the velocity profile whereas increases the temperature profile. The skin friction coefficient and the Nusselt number are inversely proportional to S . The effect of increasing values of E c is to decrease the skin friction coefficient C f and the heat transfer rate N u x . The increasing value of φ increases the skin friction coefficient and decreases the heat transfer rate.